Causes of worries of selected student teachers of the University of the Philippines their identification and relation to certain variables - Sison, Lourdes D. 1941- (s.n.], 1967)
The present study deals with one indication of anxiety, worry, which exists as an impediment to the positive drive in learning. This study identified the causes of worries in student teachers and determined the differences and relationships between worry and certain variables (i.e. age, means of support, parents' occupational level, parents' educational attainment, etc.).